Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Informasi Asimetri Dengan Variabel Kontrol Financial Disclosure dan Firm Age - Maria Yunita; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
This study aimed to know and to prove the affect of corporate social responsibility (CSR) disclosure level to information asymmetry. CSR disclosure level measured by using sustainability reporting criteria guidelines of Global Reporting Initiatives. Information asymmetry measured by bid-ask spreads. Control variables used in this research were financial disclosure and firm age.  This research was carried out on go public companies in Indonesia which published sustainability report and listed in GRI’s database with a sample of 109 observations. The results of this research asserted that CSR disclosure level has positive and significant affect on information asymmetry. The results also showed that financial disclosure did not affect information asymmetry, while firm age had negative and significant affect on information asymmetry.